1996
DOI: 10.1016/0029-7844(96)00265-7
|View full text |Cite
|
Sign up to set email alerts
|

Second-Look Operation for Epithelial Ovarian Cancer: Laparoscopy or Laparotomy?

Abstract: Laparoscopy may be an acceptable alternative to second-look laparotomy for interval evaluation of epithelial ovarian cancer. Second-look laparoscopy probably results in less morbidity, shorter operating time, shorter hospital stay, and lower total hospital charges. These results require confirmation in a randomized clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Furthermore, there are reported technical difficulties with the laparoscopic procedure, particularly when intra abdominal adhesions are present in advanced stage disease [23][24][25][26]. More importantly, there is a lack of tactile sensation which is of great importance in assessment of resectability and achievement of OCR [27][28][29]. We believe such shortcomings can be avoided by using a simple minilaparotomy as described in this paper.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, there are reported technical difficulties with the laparoscopic procedure, particularly when intra abdominal adhesions are present in advanced stage disease [23][24][25][26]. More importantly, there is a lack of tactile sensation which is of great importance in assessment of resectability and achievement of OCR [27][28][29]. We believe such shortcomings can be avoided by using a simple minilaparotomy as described in this paper.…”
Section: Discussionmentioning
confidence: 89%
“…The initial study of second-look laparoscopy reported inadequate visualization, a high false-negative rate of 11% to 55%, a high rate of complications involving primarily bowel injuries (2-9%), and a higher recurrence rate after negative second-look laparoscopy [15][16][17][18][19]. More recent studies, however, have shown that laparoscopic second-look evaluations are equivalent to those performed by laparotomy but associated with significantly lower blood loss, decreased surgical duration, fewer days of hospitalization, and lower hospital charges [21,22].…”
Section: Discussionmentioning
confidence: 97%
“…The term "second-look surgery" refers to a systematic surgical exploration performed in patients with advanced ovarian cancer who have completed a planned course of chemotherapy and are in a complete clinical remission. The surgery can be performed via laparotomy or laparoscopy with equivalent efficacy [7]. In patients with no gross evidence of tumor, multiple biopsies are obtained from the same locations as a primary staging procedure.…”
Section: Opinion Statementmentioning
confidence: 99%